2011
DOI: 10.5301/ijao.5000027
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Induced Biofilm Formation

Abstract: Surface-attached colonies of bacteria known as biofilms play a major role in the pathogenesis of device-related infections. Biofilm colonies are notorious for their resistance to suprainhibitory concentrations of antibiotics. Numerous studies have shown that subminimal inhibitory concentrations of some antibiotics can act as agonists of bacterial biofilm formation in vitro, a process that may have clinical relevance. This article reviews studies demonstrating that low-dose antibiotics induce bacterial biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
272
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(297 citation statements)
references
References 87 publications
18
272
0
7
Order By: Relevance
“…Therefore, drug susceptibility should be tested on organism in its biofilm mode and not planktonic mode to avoid treatment failure by increased antifungal tolerance and to prevent signal triggering of biofilm formation [31,32]. There was a highly significant correlation between the previous use of antifugal agents and the ability of fungi to produce biofilms (p=0.006) as well as biofilms quantities (p=0.016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, drug susceptibility should be tested on organism in its biofilm mode and not planktonic mode to avoid treatment failure by increased antifungal tolerance and to prevent signal triggering of biofilm formation [31,32]. There was a highly significant correlation between the previous use of antifugal agents and the ability of fungi to produce biofilms (p=0.006) as well as biofilms quantities (p=0.016).…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that biofilm-forming S. Infantis bacteria are able to escape in vitro the action of commonly used antibiotics. Kaplan reviewed that 'this process may have clinical relevance because bacteria are exposed to sub-MIC concentrations of antibiotics at the beginning and the end of a dosing regimen, between doses, or continuously during low-dose therapy' [33,36,37]. Knowledge about the consequences of the usage of antimicrobial agents at treatment of Salmonella infections is required to be examined and needs to be decided the concentrations considering biofilm structure.…”
Section: Resultsmentioning
confidence: 99%
“…As reviewed by Kaplan [33], although numerous studies have shown that sub-MICs of some antibiotics are not able to kill bacteria, but they can inhibit biofilm formation [33]. In contrast, many studies have shown that some antibiotics, when present at concentrations below the MIC, can significantly induce biofilm formation in variety of bacterial species in vitro.…”
Section: Dmc 7 R (32) R (64) R (128) R (32) R (128) R (32) R (32) Dmcmentioning
confidence: 99%
“…Antimicrobials are not only hindered by the biofilm matrix in their action against the microorganisms embedded in it, they may also induce the formation of biofilms dependant on the bacterial species and the antimicrobial concentration (Kaplan, 2011;Costa et al, 2012). The application of antimicrobials over a liquid feeding system therefore poses a risk of selecting antimicrobial resistant bacteria (ARB) in the biofilm by locally sub-inhibitory antimicrobial concentrations and the favourable conditions in the biofilm matrix for horizontal gene transfer (HGT) (Flemming and Wingender, 2010).…”
Section: Introductionmentioning
confidence: 99%